New providers of journalistic information in the digital environment: second-generation infomediaries - Casero-Ripollés, Andreu (Anuario ThinkEPI, 2015)
The digital environment is favouring the emergence of new providers of journalistic information. News services offered by large digital actors are analyzed, specifically FB Newswire, a platform launched by Facebook in April 2014 that distributes information content generated on social networks and publicly shared. This resource follows operating schemas that involve simultaneous cooperation and competition (coopetition) with the media. Furthermore, it is like a second-generation infomediary: in addition to connecting supply and demand, it adds a new function: as an independent information service that can potentially replace other media. This could dramatically alter the landscape of the information market in the digital environment and requires that media companies change their strategy. They must priorize the search for a differential value that gives them competitiveness and stop emphasizing news diffusion and transport as the heart of their business.
Keywords: Media information; Digital journalism; Business model; Facebook; FB Newswire; Infomediaries.